An Effective Detection Algorithm for Region Duplication Forgery in Digital Images - Yavuz, Fatih; Bal, Abdullah; Cukur, Huseyin (SPIE-INT SOC OPTICAL ENGINEERING, 2016)
Powerful image editing tools are very common and easy to use these days. This situation may cause some forgeries by adding or removing some information on the digital images. In order to detect these types of forgeries such as region duplication, we present an effective algorithm based on fixed-size block computation and discrete wavelet transform (DWT). In this approach, the original image is divided into fixed-size blocks, and then wavelet transform is applied for dimension reduction. Each block is processed by Fourier Transform and represented by circle regions. Four features are extracted from each block. Finally, the feature vectors are lexicographically sorted, and duplicated image blocks are detected according to comparison metric results. The experimental results show that the proposed algorithm presents computational efficiency due to fixed-size circle block architecture.
Keywords: Forgery detection; Discrete Wavelet Transform; Copy Move Detection; Fast Fourier Transform; COPY-MOVE FORGERY; ROBUST-DETECTION; Engineering; Optics; Physics